Post a New Question

Pre-Calculus

posted by .

translate this polar equation into a rectangular form:

rsin(2theta)=sin(theta)

My answer:

r2sin(theta)cos(theta)=sin(theta)
2rcos(theta)=1
2x=1
x=1/2

This is the only answer I can get and someone told me it's wrong. Would someone please help me with this

  • Pre-Calculus -

    or maybe the answer is:

    y=2xy

    but that's kind of weird

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    change equations to polar form: 1) y= -1 2) x^2 + y^2 = 4 how would i do these questions?
  2. Algebra II

    Which of the following expressions are not equal to 1?
  3. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  4. Advanced Math

    Identify the polar form of the linear equation 4x+3y=10. x=rcos(theta),y=rsin(theta) 4x+3y=4rcos(theta)+3rsin(theta)=10 r=10/(4cos(theta)+3sin(theta) I got it wrong
  5. trigonomtry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  6. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  7. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  8. Algebra II

    Multiple Choice Which expression is NOT equivalent to 1?
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions

Post a New Question